Heterogeneity of FHF1 related phenotype: Novel case with early onset severe attacks of apnea, partial mitochondrial respiratory chain complex II deficiency, neonatal onset seizures without neurodegeneration. (September 2017) - Villeneuve, Nathalie; Abidi, Affef; Cacciagli, Pierre; Mignon-Ravix, Cécile; Chabrol, Brigitte; Villard, Laurent; Milh, Mathieu
Abstract: Introduction/objectives: We report the case of a child prospectively followed in our institution for a severe, neonatal onset epilepsy presenting with severe attacks of apnea that were not initially recognized as seizure since they were not associated with any abnormal movement and since interictal EEG was normal. Recording of attacks using prolonged video-EEG recording allowed to confirm the diagnosis of epileptic seizures. Results: Using whole exome sequencing we found a de novo heterozygous, missense mutation of FHF1 (p.Arg52His, NM_004113), a mutation that has been very recently described in 7 patients with an early onset epileptic encephalopathy. The initial workup showed a partial deficit of the complex II of the respiratory chain in muscle and liver. The prospective follow-up demonstrated that 2 drugs seemed to be more effective than the others: sodium blocker carbamazepine, and serotonin reuptake blocker fluoxetine. GABAergic drugs seemed to be ineffective. No drug aggravated the epilepsy. Discussion: This case report contributes to the description of an emerging phenotype for this condition. Highlights: A recurrent mutation of FHF1 was found in a patient with neonatal onset epilepsy. Seizures were initially mistaken for attacks of central apnea with cyanosis. Video-EEG recording revealed ongoing focal seizure involving frontal and temporal lobes. Seizure decreased with sodium channel blockers and serotonin uptake blockers. Brain MRI did not show any neurodegeneration during the follow-up.